Educational stage of the formation of the youth social activity system in civil society institutes - Stupak, Oksana (ScienceRise: Pedagogical Education, 2020)
The article describes the content of the educational stage of the system of formation of social activity of youth in civil society institutions. This stage involved the formation of basic ideas of young people about the structure, content, directions, projects of civil society institutions; mastering of knowledge and acquisition of planning skills, organization of activity of civil society institutions; systematization of knowledge about the role of youth in the development of civil society, models of youth participation in public life. Among the main projects and invents, implemented within this stage, the following are presented in the article: regional stages of the International Program “Student Republic” on “Positive scenarios for the modernization of the Donetsk region: the role of communities and youth” and “Education – a key focus of the new industrialization of the Donetsk region” (students discussed important issues in the region and worked out their own solutions); regional event “The best students of Donetsk region” (students with academic, social, social and sporting degrees in higher education institutions are recognized); project “Civic Education of Youth in Ukraine” (conducting a series of educational events for young people on the means of realization of civic youth activity, skills of project activity, interaction with the authorities during public activity, the participants of which had the opportunity to participate in the competition of projects for receiving mini-grants); project “Workshop for Active Youth: East and West Together” (thematic trainings, workshops on topical issues: e-governance, decentralization, youth participation in decision-making processes, opportunities for youth, project management etc.). The study also presents a series of trainings and debates, conducted with the youth of eastern Ukraine to formation their social activity